La efectividad de la terapia de aceptación y compromiso como tratamiento para el trastorno de ansiedad social: revisión aplicada - Zavala Rodriguez, Gabriel (2023)
Currently, the efficacy of cognitive behavioral therapy is known, which is why it is positioned as the first option for the treatment of different disorders. One of them is social anxiety disorder, a frequent disorder that is increasing considering the current digitalized context. However, there is a significant group of clients who do not respond or are remittent to treatment. Therefore, the objective of this study is to identify the efficacy of acceptance and commitment therapy in the treatment of social anxiety disorder. An exhaustive review of scientific articles that evaluated both variables was carried out, for which 10 investigations were selected from the Web of Science, Scopus, Scielo and Ebsco databases. The results show that acceptance and commitment therapy is effective for social anxiety disorder, reaching almost the same level of effectiveness as cognitive behavioral therapy. It not only helps to reduce symptoms but also influences the development of other skills.